Pelatihan Perhitungan Metode Statistical Quality Contol untuk Mengurangi Produk Cacat pada Bisnis M-Prod - Resi Juariah Susanto (BADAN PENERBIT STIEPARI PRESS, 2023)
Nowadays, MSMEs are very easy to start, so competition in business is getting tougher in the eyes of consumers. This community service was carried out with the aim of reducing the number of defective products produced by MSMEs so that production can run well and losses in the production process are lower. This service is carried out at M-Prod MSMEs by providing direct assistance or practice in calculating the emphasis on defective products using the Statistical Quality Control (SQC) method. The problem often faced by MSME M-Prod players is that quite a large number of damaged goods are still found. By using the SQC method, it is hoped that it can help business actors to reduce defective products. So that in the future the business can run even better. The output targets to be achieved are in the form of publications in journals and increasing the understanding and skills of business actors.